A review of Anapausis Enderlein (Diptera: Scatopsidae) in the Neotropical Region, with four new species and comments on the phylogeny of the genus - Amorim, Dalton D.s.; Balbi, Maria I.p.a. (Zootaxa, 2006)
Four new Neotropical species of Anapausis are described: A. clivicola sp. nov., A. wirthi sp. nov., A. mayana sp. nov., and A. mourei sp. nov. Anapausis fuscinervis Edwards is redescribed, and a key for the Neotropical species of the genus is provided. The homology of the sclerites of the male terminalia is considered. Shared features allow recognition of four major clades within the genus, one composed of the species in Australia, New Zealand, Chile, and southern Brazil, one composed of a pair of Central American species, one composed of the Afrotropical and Oriental species, and one composed of the Holarctic species. The Central American species of Anapausis appear to be more connected to the circumantarctic and the Afro-Oriental clades than to the Holarctic clade of the genus.